Ultraviolet-Induced Fluorescence and Sub-Ultraviolet Reflectance Dermatoscopy of Grover’s Disease (Transient Acantholytic Dermatosis): a Retrospective Single-Center Cohort Study - Pietkiewicz, Paweł; Navarrete-Dechent, Cristian; Adarsha , Adhikari; Cantisani, Carmen; Goldust, Mohamad; Salwowska, Natalia; Kiss, Norbert (Dermatology Practical & Conceptual, 2025)
Introduction: Grover's disease (GD) is a rare acantholytic skin disorder typically characterized by pruritic vesicular or keratotic truncal papules, most commonly affecting older Caucasian males. Ultraviolet-induced fluorescence dermatoscopy (UVFD) and sub-ultraviolet reflectance dermatoscopy (sUVRD) are novel imaging techniques with potential diagnostic value in dermatology. Objectives: The objective of this study was to evaluate the dermatoscopic patterns of GD using UVFD and sUVRD techniques. Methods: A retrospective single-center cohort observational study was conducted including consecutive adult patients diagnosed with GD. Dermatoscopic images were obtained using a Dermlite DL5 dermatoscope paired with a smartphone for UVFD and a Casio DZ-D100 Dermocamera for sUVRD. Results: Among the 23 investigated patients (15 females, eight males; mean age 49.13 years), UVFD images frequently showed central polygonal bright scales with a greenish background. sUVRD images demonstrated hyporeflective polygonal scales, hyperreflective halos, and vascular patterns at the periphery. sUVRD was superior to UVFD and CD in the detection of semi-specific polygonal scales in GD. Eccrine duct involvement was observed in 76.31% of sUVRD images and 57.89% of matching conventional polarized dermatoscopy images. Contrary to the existing literature, female patients represented a higher percentage of the cohort. Twelve GD patients (52.2%) had a personal history of skin cancer, Conclusion: UVFD and sUVRD effectively characterized the unique features of GD lesions. Our findings suggest that GD may affect younger individuals and females more frequently than previously reported, potentially indicating underdiagnosis in this population. Incorporating dermatoscopy into routine examinations may improve the detection and management of GD.